2018
DOI: 10.1073/pnas.1804224115
|View full text |Cite
|
Sign up to set email alerts
|

Climate change causes upslope shifts and mountaintop extirpations in a tropical bird community

Abstract: Montane species worldwide are shifting upslope in response to recent temperature increases. These upslope shifts are predicted to lead to mountaintop extinctions of species that live only near mountain summits, but empirical examples of populations that have disappeared are sparse. We show that recent warming constitutes an “escalator to extinction” for birds on a remote Peruvian mountain—high-elevation species have declined in both range size and abundance, and several previously common mountaintop residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
375
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(397 citation statements)
references
References 46 publications
(48 reference statements)
16
375
1
5
Order By: Relevance
“…This pattern was consistent across all AOGCM and with studies showing that species with higher fecundity may be buffered against a decrease in their overall range of occurrence (e.g., Amano & Yamamura, 2007). have shown that mountain bird species will lose a greater range of occurrence than other species (e.g., La Sorte & Jetz, 2010;Freeman, Scholer, Ruiz-Gutierez, & Fitzpatrick, 2018; see also a meta-analysis by Scridel et al, 2018). A possible reason for the difference between our results and those from other studies is that our data- Finally, had we assumed dispersal limitation in our ENMs, our estimates of range shift would be even greater (depicting a more pessimistic scenario) because dispersal limitation would make it difficult for species to track their optimal conditions in space (Hof & Allen, 2019;Wang, He, Thompson, Spetich, & Fraser, 2018).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This pattern was consistent across all AOGCM and with studies showing that species with higher fecundity may be buffered against a decrease in their overall range of occurrence (e.g., Amano & Yamamura, 2007). have shown that mountain bird species will lose a greater range of occurrence than other species (e.g., La Sorte & Jetz, 2010;Freeman, Scholer, Ruiz-Gutierez, & Fitzpatrick, 2018; see also a meta-analysis by Scridel et al, 2018). A possible reason for the difference between our results and those from other studies is that our data- Finally, had we assumed dispersal limitation in our ENMs, our estimates of range shift would be even greater (depicting a more pessimistic scenario) because dispersal limitation would make it difficult for species to track their optimal conditions in space (Hof & Allen, 2019;Wang, He, Thompson, Spetich, & Fraser, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…However, studies have shown that mountain bird species will lose a greater range of occurrence than other species (e.g., La Sorte & Jetz, 2010;Freeman, Scholer, Ruiz-Gutierez, & Fitzpatrick, 2018; see also a meta-analysis by Scridel et al, 2018 argue that our estimates of potential geographic range loss would be lower after allowing for adaptation. For UKMO, these species were projected to lose a smaller range of occurrence than species classified with a smaller extinction risk.…”
Section: Discussionmentioning
confidence: 77%
“…Modelling work on the future effects of climate and land use change have suggested that species‐specific conservation measures aiming at improving habitat to counteract the negative influence of climate change can only deliver minor improvements of the future fate of mountain birds (Braunisch et al, ). Even if high mountains may provide refuges for threatened mountain species currently populating lower altitudes, in the long term, climate change can be expected to have a strong impact on alpine species (Freeman, Scholer, Ruiz‐Gutierrez, & Fitzpatrick, ). Alpine habitats are expected to be reduced and become more fragmented and isolated due to rise of the tree line where species have increasing limited dispersal possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies documented downslope shifts in species distributions, associated with changes in precipitation, land use and other elevation-correlated gradients Grenouillet 2013, Radinger et al 2016). These shifts will alter biodiversity patterns, with eroded richness at low elevation, mountaintop extinctions at high elevations, and changes in species' cooccurrences and subsequent interactions at all elevations (Feeley and Silman 2010, Sheldon et al 2011, Freeman et al 2018.…”
Section: Introductionmentioning
confidence: 99%